Role of Renal Ultrasonography in Early Detection of Acute Kidney Injury in Neonates with Sepsis - Abdaljabar, Mazin Qais; Shibat, Shaimaa Hasoon Shibat; Abd Alhassan, Majid Abd Alhassan (Academic Journal of Clinicians, 2023)
Background: Sepsis, is one of the risk factors for newborn acute kidney injury (AKI). Ultrasonography (US) is the main imaging technique used to assess the renal function problems in newborns due to its benefits of being portable and noninvasive. Objective: To assess the validity of renal ultrasonography findings in early detection of AKI in neonatal sepsis Patients and methods: This cross-sectional study was conducted in neonatal intensive care unit in Karbala teaching hospital for children, holly Karbala, Iraq for the period from 3rd of January 2021 to the 31st of December 2021. The study included07 full term neonates with signs and symptoms of sepsis. The results of urinalysis, automated , and C-reactive protein (CRP) were collected and renal ultrasound performed within maximum of 3 days from hospitalization. Validity of ultrasound was assessed based on the validity parameters using standard equation. P. value ≤ 0.05 considered significant. Results: Compared to GUE, renal ultrasonography showed good sensitivity , specificity , accuracy and negative predictive value (NPV) but low positive predictive value (PPV). Compared to CRP or WBC , renal ultrasonography was low sensitive, specific and accurate. When renal ultrasonography compared to combined WBC and CRP, it showed low sensitivity (33.3%) , low accuracy and very low NPV but 100% specificity and 100% PPV Conclusion: Renal U/S shows pathological changes in the kidney of some neonate with sepsis. these changes in the U/S can support the diagnosis of sepsis but not to rely on as an independent tool in diagnosis of sepsis alone .